"A Conspiracy of the Nation": Case Study of Stokely Carmichael's and H. Rap Brown's Arguments in Support of Black Power. (January 2020) - Galloway, Lauren F. E.
This article features a rhetorical analysis of the Student Nonviolent Coordinating Committee's (SNCC) transition from nonviolent resistance to a more militant ideology, evidenced through prominent works by the organization's last two chairmen, Stokely Carmichael and H. Rap Brown. I argue the chairmen's conspiracy rhetoric contended with widespread interpretations of the times that framed SNCC's decision as purely irrational, as opposed to a choice arising out of a long history of racial oppression. Furthermore, contentious media portrayals of SNCC demonstrators as ungrateful, heretical, sectarians aligned closely with readily accepted racial stereotypes to justify nonsupport of the pursuit of equality for Black Americans, civil or otherwise. This contribution to the literature conjures up challenges and tactics of movements past to inform the rhetorical strategies of present-day activists.